Exclusive Breastfeeding and Nutritional Status of Toddlers in a Community Health Center - Riza Yanti; Umi Faridah; Muhamad Jauhar (CV Media Inti Teknologi, 2025)
Background: The nutritional status of toddlers serves as a key marker of their overall health and development, influencing cognitive abilities, immune function, and long-term productivity. Exclusive breastfeeding in the first six months is essential for supporting and enhancing nutritional well-being during early childhood. Nevertheless, public understanding of the critical benefits of exclusive breastfeeding is still limited.Aims: This study aimed to analyze the relationship between exclusive breastfeeding and the nutritional status of toddlers in the working area of Dawe Public Health Center, Kudus Regency.Methods: This study employed a quantitative analytic approach with a cross-sectional design. A total of 71 mothers with toddlers were selected through random sampling. Exclusive breastfeeding served as the independent variable, while the toddler’s nutritional status was the dependent variable, measured using the Kartu Menuju Sehat (KMS) growth chart. Data collection was conducted through questionnaires and document analysis, and the results were analyzed using the chi-square statistical test.Results: The results of the analysis revealed a statistically significant association between exclusive breastfeeding and toddlers' nutritional status, as evidenced by a p-value of 0.001 (p < 0.05). This suggests that toddlers who were exclusively breastfed were more likely to exhibit better nutritional outcomes.Conclusion: A significant correlation exists between exclusive breastfeeding and the nutritional status of toddlers. Consequently, it is essential to enhance health education efforts for mothers regarding the benefits of exclusive breastfeeding. In addition, ongoing support from healthcare providers is crucial to increase awareness and promote better exclusive breastfeeding practices within the community.